The association between pregnancy spacing and iron deficiency anemia at RSUD Dr. Moewardi - Damayanti, Puspa; Sunaryo, Rustam; Murti, Bhisma (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
ABSTRACT Background: Pregnant women to be one of those most vulnerable to malnutrition, especially iron deficiency anemia and iron deficiency anemia coping is currently focused on the tablet of iron (Fe) in pregnant women. While pregnancy distance of less than 2 years old are at greatest risk for iron deficiency anemia. Methods: This analytic study was observational using case-control approach. A sample of 60 study subjects was selected by purposive sampling and fixed disease sampling from outpatients who visited Obstetric Clinics, RSUD Dr. Moewardi Surakarta. The data was collected by interview and some datas taken from the medical records. The data was analyzed using multiple logistic regression model on SPSS 20 for windows. Results : The pregnant women with pregnancy spacing â¥ 24 months at RSUD Dr. Moewardi have a greater risk for iron deficiency anemia 0,8 times larger than <24 months pregnancy spacing (OR=0,8 ; Cl 95% 0,17 s.d. 3,80; p=0,778). This analysis have control gestational age as a confounding factor, but not control the intake of nutrient. Conclusion: There is a weak and negative association, and not statistically significant between the gestational age with iron deficiency anemia.. Keywords: pregnancy spacing, iron deficiency anemia